Francois X. Martin, A Collection of Statutes of the Parliament of England in Force in the State of North Carolina 60-61 (1792) - (:unkn) unknown (My University, 1792)
Restatement of the Statute of Northampton, prohibiting going armed with force and arms in affray of peace, nor to go nore ride armed by night nor by day in fairs, markets, nor "in the presence of the King's Justices.
Keywords: GOING ARMED